Trilingual Education: An Effective Way of Providing Inclusion - Kulsariyeva, Aktolkyn; Iskakova, Aigul; Tajiyeva, Marzhan (European Scientific Journal, ESJ, 2017)
The aim of this article is to study the problem of multilingual communication and the equal access to information which is relevant especially today due to the integration processes taking place in the world. Our society, just like other parts of the world, is interested in learning English. This is traceable to the fact that most people are now seeking to master the language. They have the highest communication value which is reflected in public documents such as SDPES (State Development Programme for Education and Science) for 2016-2019. These include the main trends of the development of trilingual education and the adopted Roadmap of trilingual education from years 2015-2020. Their aim is to ensure the gradual introduction of the trilingual education at all levels of education in Kazakhstan. In this regard, the MES developed a common strategy for training trilingual teachers. For example, from the perspectives of pedagogical university (Abai Kazakh National Pedagogical University), authors present the stages of implementation of the process based on the following priority areas: improving the legal and methodological framework; update of educational programs; the creation of a unified system of training; and professional development of teaching and administration staff.